Research Mapping of Musyarakah Contracts in Islamic Financial Institutions: VOSviewer Bibliometric Study and Literature Review - Eka Wahyu Hestya Budianto; Nindi Dwi Tetria Dewi (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to determine the map of research developments regarding Musyarakah contracts in Islamic Financial Institutions with VOSviewer bibliometric study and literature review. The research was carried out for a period of 17 years from 2005 to 2021 by searching through the Garuda website (Garba Reference Digital) for the key to Musyarakah. And obtained 310 research articles. The search results were then analyzed descriptively and inputted to find out the visualization of the mapping of the development of topics and research subjects around the Musyarakah contract. The results of the study indicate that the number of publications regarding Musyarakah contracts has increased significantly every year, and based on the results of mapping visualization using VOSviewer, research on Musyarakah contracts is divided into 5 clusters. Meanwhile, based on the results of the literature review, there are 8 main themes and 124 research topics regarding Musyarakah contracts in Islamic Financial Institutions.